2022
DOI: 10.3390/cancers14051194
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cancer Effects following Ionizing Irradiation Involving the Eye and Orbit

Abstract: The eye is an exemplarily challenging organ to treat when considering ocular tumors. It is at the crossroads of several major aims in oncology: tumor control, organ preservation, and functional outcomes including vision and quality of life. The proximity between the tumor and organs that are susceptible to radiation damage explain these challenges. Given a high enough dose of radiation, virtually any cancer will be destroyed with radiotherapy. Yet, the doses inevitably absorbed by normal tissues may lead to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…Azizova et al [ 19 ] reported a significantly increased radiation risk of normal-tension glaucoma (a subtype of primary open-angle glaucoma) in a cohort of Russian Mayak nuclear workers, confirming observations in Japanese atomic bomb survivors [ 42 , 43 , 44 ]. Thariat et al [ 20 ] reviewed the current knowledge on normal tissue complications in the eye and orbit (e.g., the lacrimal gland, eyelashes, eyelids, cornea, lens, macula/retina, optic nerves and chiasma) following radiotherapy. Peuker et al [ 21 ] found a sigmoidal relationship between radiation dose and the incidence of inner ear toxicity following radiotherapy for nasopharyngeal carcinoma, and proposed dose constraints to reduce inner ear toxicity.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Azizova et al [ 19 ] reported a significantly increased radiation risk of normal-tension glaucoma (a subtype of primary open-angle glaucoma) in a cohort of Russian Mayak nuclear workers, confirming observations in Japanese atomic bomb survivors [ 42 , 43 , 44 ]. Thariat et al [ 20 ] reviewed the current knowledge on normal tissue complications in the eye and orbit (e.g., the lacrimal gland, eyelashes, eyelids, cornea, lens, macula/retina, optic nerves and chiasma) following radiotherapy. Peuker et al [ 21 ] found a sigmoidal relationship between radiation dose and the incidence of inner ear toxicity following radiotherapy for nasopharyngeal carcinoma, and proposed dose constraints to reduce inner ear toxicity.…”
Section: Overview Of Published Articlesmentioning
confidence: 99%
“…Therefore, this Special Issue ( ) aims to serve as a forum to gather the latest developments and discuss future prospects in the field of normal tissue responses to radiation exposure. The Special Issue consists of 18 articles [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] outlining the cancer and non-cancer effects of radiation occurring in various tissues (e.g., those in the circulatory, sensory, nervous, respiratory, and reproductive systems), including studies on mitigation strategies and biomarkers, as outlined below.…”
Section: Introductionmentioning
confidence: 99%
“…As more centers treat UM with photon-based SRT and the number of proton centers worldwide increases, the patient selection based on the potential trade-off in toxicities needs to be addressed. The choice of the optimal technique should account for both the risk of post-treatment complications [26] and quality-of-life [27] . However, direct photon-proton plan comparison studies are not possible due to differences in treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Although gamma knife radiosurgery and proton therapy are effective treatments with reliable tumor control rates, they are associated with poor visual outcomes, inadequate globe retention, and their use is reportedly limited to the public health system of low- or middle-income countries [ 5 , 6 ]. EBRT carries the risk of significant side effects related to a broader radiation field and increased risk of complications ocular and periocular structures such as eyelids, sclera, lens, and retina [ 7 ]. Finally, enucleation is an effective management for very large tumors and usually a last resource.…”
Section: Introductionmentioning
confidence: 99%